Laparoscopic repair of amyand hernia – A case report with review of literature - Agrawal, Prachi; Joshi, Abhijit S (Eastern Journal of Medical Sciences, 2025)
Amyand’s hernia is a rare condition in which the appendix becomes incarcerated within an inguinal hernia. Although this type of hernia is uncommon, it can lead to serious complications such as strangulation and perforation when the appendix becomes trapped. Incarceration of the appendix is most frequently observed in inguinal and femoral hernias, but it can also occur, though less commonly, in incisional and umbilical hernias. This case report describes an 83-year-old male, who was diagnosed with a right inguinal hernia and underwent laparoscopic hernia repair. Intraoperatively, a right-sided Amyand’s hernia was identified. Since the appendix was not inflamed, it was reduced and a mesh plasty was performed to repair the hernia. The patient had an uneventful recovery.